Penentuan Masa Simpan Ekstrak Etil Asetat Buah Andaliman Pada Kemasan Botol Kaca dan PET dengan Metode Accelerated Shelf-Life Test (ASLT) - Lubis, Siti Basyariah Putri; Julianti, Elisa; Siagian, Albiner (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Andaliman is an endemic flora in the region around Lake Toba and is commonly used as a spice by the Batak ethnic community. Andaliman fruit in extract form has a lot of potential as an antimicrobial, anti-inflammatory and antioxidant. All the benefits possessed by andaliman extract have the potential to be widely used by the community. Therefore, it is important to know the shelf-life of the extract and the most suitable type of packaging to extend its shelf-life. This study aims to estimate the shelf-life of andaliman fruit extract and the packaging that can extend the shelf-life of the extract. The estimated shelf-life was calculated using the accelerated shelf-life test (ASLT) method using Arrhenius approach with the parameter of total flavonoids. This study used two types of packaging, namely glass bottle and plastic bottle stored at 37, 45, and 55 °C for 1 month with weekly testing. The results showed that andaliman fruit extract in plastic bottle packaging can last for 7.8 months at 37 °C and 6.8 months at 55 °C. While stored in glass bottle, andaliman fruit extract can last up to 12.4 months at 37 °C and 10.5 months at 55 °C. Based on these data, it is known that the shelf-life of extracts is influenced by storage temperature and packaging.  The higher the temperature, the shorter the shelf-life and the smaller the permeability, the longer the shelf-life.